Bioethics in current Medical Ethics Code - Neves, Nedy Maria Branco Cerqueira (2010)
This article aims to analyze and discuss the incorporation of Bioethics references in the present Medical Ethics Code adopted by the Federal Council of Medicine after two years of study. A research was carried out for all objects in the current code to verify which Bioethics foundations were included, seeking to accomplish a critical reflection from this investigation. Bioethics principles related to issues like autonomy, justice, beneficence/non-maleficence was widelycovered in the new text. Other references were also observed, such as citizenship, human dignity, responsibility, and conflict of interest. In the Fundamental Principles were noted other core values relating to health care, respect, consideration, human rights, solidarity, non discrimination and research on human beings. In authors’ opinion, it was demonstrated that professionals desire to establish doctor-patient relationships supported by ethical conduct. The new instrument sought to establish a balance between the maximum morality and the minimum morality of conformity to mandatory standards.